2020
DOI: 10.3390/agronomy10040547
|View full text |Cite
|
Sign up to set email alerts
|

Poaceae with PGPR Bacteria and Arbuscular Mycorrhizae Partnerships as a Model System for Plant Microbiome Manipulation for Phytoremediation of Petroleum Hydrocarbons Contaminated Agricultural Soils

Abstract: Total petroleum hydrocarbons (TPHs) are a persistent environmental organic contaminant. The possibility of obtaining synergistic effects between plants and microorganisms has further increased the possibility of alternative techniques for bioremediation. Oloptum miliaceum (L.) Röser & H.R. Hamasha and Pennisetum setaceum (Forssk.) Chiov. are, undoubtedly, good model plants for phytoremediation because they have large roots, leaf biomass, and a fast and effective renewal capacity, also, they have a great ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…After 270 days, MDA level decreased in leaf samples of all the investigated plant species. These findings are in accordance with other research highlighting that MDA levels in leaves increased with increasing crude oil concentration in soil and decreased with exposure time ( Shukry et al, 2013 ; Guarino et al, 2020 ). The decreasing MDA trend over time may indicate that, under hydrocarbons’ degradation, repairing mechanisms start to keep pace with oxidative damage.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…After 270 days, MDA level decreased in leaf samples of all the investigated plant species. These findings are in accordance with other research highlighting that MDA levels in leaves increased with increasing crude oil concentration in soil and decreased with exposure time ( Shukry et al, 2013 ; Guarino et al, 2020 ). The decreasing MDA trend over time may indicate that, under hydrocarbons’ degradation, repairing mechanisms start to keep pace with oxidative damage.…”
Section: Resultssupporting
confidence: 93%
“…These results indicate that the uptake of petroleum hydrocarbons in roots is enhanced through a rhizodegradation mechanism. In rhizodegradation, organic pollutants are degraded in soil through the bioactivity of the rhizosphere, which derives from the production and exudation of enzymes and proteins by plants or soil microorganisms such as bacteria or fungi ( Guarino et al, 2020 ). The lower levels of TPH in leaves may be related to the hydrocarbons phytotransformation or phytodegradation occurring within the plant itself.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endophytic fungi can produce various phytohormones, such as phytohormone indole-3-acetic acid, gibberellic acid, cytokinin, and phytoalexins, which were successively found from the endophytic fungi Serendipita indica , F. fujikuroi MI58289, and Piriformospora indica DSM11827 (Inaji et al 2020 ; Niehaus et al 2016 ; Li et al 2016b ). This finding indicated that endophytic fungi can participate in host signal regulation and affect host physiological and metabolic activities (Yuan et al 2016 ; Bilal et al 2018 ; Guarino et al 2020 ).…”
Section: Research Progress On the Biosynthesis Of Natural Products By Endophytic Fungimentioning
confidence: 99%